2016
DOI: 10.1002/lary.26254
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic variations in normal and fibrotic human laryngotracheal‐derived fibroblasts: A Warburg‐like effect

Abstract: Objective/Purpose Laryngotracheal stenosis (LTS) is a chronic fibrotic disease characterized by fibroblast proliferation, collagen deposition, and matrix remodeling in the lamina propria of the larynx and/or trachea. Current medical therapies are limited by a poor understanding of the effector cell’s (fibroblasts) cellular biology and metabolism. The purpose of this study is to compare cellular proliferation, function, and metabolism between normal and LTS-derived fibroblasts in vitro. Methods Human biopsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…8 Recent studies have shown that compared to normal fibroblasts, fibroblasts isolated from laryngotracheal scar proliferate faster, exhibit metabolic changes, and express more collagen. 9 This echoes the fibrotic phenotype observed in other organs. In cardiac fibrosis, fibroblasts transdifferentiate into myofibroblasts in response to ischemic injury, producing excessive ECM and a contracted scar.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…8 Recent studies have shown that compared to normal fibroblasts, fibroblasts isolated from laryngotracheal scar proliferate faster, exhibit metabolic changes, and express more collagen. 9 This echoes the fibrotic phenotype observed in other organs. In cardiac fibrosis, fibroblasts transdifferentiate into myofibroblasts in response to ischemic injury, producing excessive ECM and a contracted scar.…”
Section: Introductionsupporting
confidence: 64%
“…31 This allows fibroblasts to shift its energy production from an oxygen-dependent pathway to an oxygen-independent pathway, creating the Warburg-like effect that we’ve previously described in our scar fibroblasts. 9 …”
Section: Discussionmentioning
confidence: 99%
“…All biopsies were obtained by the same surgeon, with source tissue initially identified by visual inspection. Primary fibroblasts were isolated from the biopsy specimens, cultured, and expanded—and then experiments were performed with passage 2 or 3 cells, as in earlier work . Cellular phenotype was confirmed through immunohistochemical staining, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…However, the underlying differences in these fibroblasts are poorly understood, including biologic and metabolic differences between scar and normal laryngotracheal fibroblasts. Recent evidence indicates that there are distinct abnormalities in iLTS scar fibroblasts when compared to normal airway fibroblasts from the same patient . iLTS scar fibroblasts are hyperproliferative, have increased extracellular matrix (ECM) deposition, and demonstrate a metabolic shift to reduced oxidative phosphorylation and increased aerobic glycosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation